Gastro-bronchial fistula. Issue 586 (August 1974) - Missen, Anthony J. B.; Pemberton, James; Boon, Andrew
Abstract : 1. Gastro-bronchial fistula is a rare condition occurring most commonly as a complication of a subphrenic abscess. 2. Other causes include trauma and necrosis within an infiltrating neoplasm. 3. The treatment of those fistulae which are secondary to a subphrenic abscess should be by drainage of the abscess, jejunal tube feeding and continuous gastric aspiration.